(untitled) (Missouri, 1996)
The Manual of Staff Development is a practical resource that provides staff development educators and administrators with a compendium of useful tools and techniques to meet the rapidly changing professional development needs of their staff. Drawn from hospitals throughout the U.S. and Canada, the materials address such crucial and diverse activities as staff development certification, finance, quality, marketing, instructional design, needs assessment, program planning, orientation, preceptorship, inservice education, competence assessment, and evaluation. This resource enables the staff development educator to benefit from the expertise and experience of numerous staff development experts, saving the time and money required to create these programs and materials.
Keywords: Employees,Nhân viên; Training of,Sự huấn luyện